THE MEDIATING ROLE OF EMOTIONAL INTELLIGENCE ON JOB STRESS AND EMPLOYEE PERFORMANCE - Gabriella Panjaitan; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This critical review examines the mediating role of emotional intelligence (EI) in the well-established relationship between job stress and employee performance. While the direct negative impact of stress on performance is well-documented, this article synthesizes existing literature to argue that EI acts as a crucial psychological buffer in this dynamic. The analysis differentiates between ability and trait models of EI and elucidates the "stressor-detachment" pathway—whereby high-EI individuals appraise stressors as challenges, effectively regulate emotions, and achieve psychological detachment, thereby preserving cognitive resources and performance. The findings suggest that EI is not merely a direct predictor but a key mechanism that explains significant variance in how stress impacts workplace outcomes. The review concludes that organizations should prioritize developing EI as a strategic intervention to enhance employee resilience and maintain performance in demanding work environments